Regulation of Commercial Space Transport: The Astrocizing of ICAO - Abeyratne, Ruwantissa (Springer, 2016)
This book provides a look at the various nuances of the commercial aspects of space transport and offers a workable and practical legal and regulatory approach to be taken by the International Civil Aviation Organization. The book also addresses the perceived lack of wisdom in neglecting to consider the basic legal structure of a regulatory regime for commercial space transport as a first step and goes on to analyze ways and means of using the existing legal instruments pertaining to international civil aviation as an analogous system that can be moulded into a separate and cohesive set of multilateral legal instruments that could apply to commercial space transport. As expected, commercial space transport has taken off with a flourish. It is now evident that, from sub-orbital flights to mining asteroids, this industry will grow exponentially. Signs of its importance are reflected by various international conferences being convened on the subject both by academia and the international community. The only snag is the lack of a regulatory instrument or in the least a contrived approach to a definitive legal regime that would provide a structure, purpose and direction to commercial space transport. This blatant lacuna and neglect has resulted in the emergence of various theories by academics and a half hearted look at the subject by the international legal community.